PROFIL PERBEDAAN LEVEL MATHEMATICS ANXIETY MAHASISWA CALON GURU SEKOLAH DASAR - A. WIlda Indra Nanna (Universitas Borneo Tarakan, 2021)
Mathematical anxiety can also be found in pre service teachers who are currently taking courses related to mathematics. This study aims to describe the profile of the level of mathematics anxiety among pre-service elementary schools from the differences in majors in high school. A descriptive quantitative design was used in this research. The research subjects were 105 pre-service elementary teachers (PSETs) of the first batch in the PGSD study program. The data collection technique was carried out by distributing the RMANX questionnaire and then analyzed using descriptive statistics. The findings of the study were: a) Mathematics anxiety among PSETs from the science department, 18% were in the high category, 67% were in the moderate category, and 15% were in a low category; b) For PSETs from the social studies department, the level of mathematics anxiety is 20% in the high category, 65% in the medium category, and 15% in the low category; c) For PSETs from the vocational school major, obtained 25% high category, 67% medium category, and 8% low category; d) On average, pre-service elementary teachers have anxiety about mathematics at the moderate level category